Study on Governance and Service of the In-Service Teacher Certification Program for Raudhatul Athfal from the Perspective of PPG (Teacher Professional Education) Participants - Munastiwi, Erni; Sumarni, Sri (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2023)
Purpose – This research aims to examine various aspects related to the implementation of the In-Service Teacher Professional Program (PPG) for Raudhatul Athfal teachers at UIN Sunan Kalijaga Yogyakarta, including the program's administrative procedures, governance structure, program implementation, and the outcomes resulting from the program's implementation. Design/methods/approach – Conducted at UIN Sunan Kalijaga Yogyakarta in 2022, this study utilized a case study design. A mixed approach combining qualitative and quantitative methods was employed to analyze the management and implementation of the PPG for Raudhatul Athfal teachers. Research participants and respondents included program managers, partner lecturers, and program participants. Findings – The study reveals that the administration and governance of the In-Service PPG program were implemented efficiently and effectively, facilitated by information technology and cooperation among various government entities and educational institutions. The implementation of this program has shown improvements in participants' competencies, such as understanding early childhood education and developing teaching skills. The outputs from this program include competency development in designing and implementing appropriate learning for young children, involving parents, and integrating religious values. Research implications– The findings of this study underscore the importance of enhancing teachers' competencies and professionalism to improve education quality in Indonesia. However, certification programs like the In-Service PPG represent only one aspect of enhancing teacher professionalism; other necessary steps include post-certification quality assurance and continuous development for teachers. This study also highlights the significance of programs like the In-Service PPG in achieving these goals.